ANALISIS PENGARUH MATA KULIAH ENTREPRENEURSHIP TERHADAP MINAT MAHASISWA DALAM BERWIRAUSAHA (STUDI KASUS: AMIK “BSI PONTIANAK”) - Latifah Latifah; Nurmalasari Nurmalasari (Universitas Bina Sarana Informatika, 2013)
This study aimed to determine the effect of Entrepreneurship courses in the interest of students to Entrepreneurship in the AMIK “BSI Pontianak”. This research background of curiosity towards the course Entrepreneurship extent been able to influence and motivate students to develop business and have a high interest towards Entrepreneurship. The method used is the method of survey and data collection tool using a questionnaire. The number of population in the set of 100 respondents. The results of this study indicate that subjects generally entrepreneursip to increase student interest in Entrepreneurship, provide insight and an overview of the business opportunity as well as theories that equip students to compete in the business world later.Key words: Entrepreneurship, interest of entrepreneurship, entrepreneurship courses